On the Determination of the Aerodynamic Damping of Wind Turbines Using the Forced Oscillations Method in Wind Tunnel Experiments - Robert Fontecha (Energies, 2019)
The development of wind turbine technology has led to higher and larger wind turbines with a higher sensitivity to dynamic effects. One of these effects is the aerodynamic damping, which introduces favorable damping forces in oscillating wind turbines. These forces play an important role in the turbine lifetime, but have not yet been studied systematically in detail. Consequently, this paper studies the plausibility of determining the aerodynamic damping of wind turbines systematically through wind tunnel experiments using the forced oscillation method. To this end, a 1:150 scale model of a prototype wind turbine has been fabricated considering Reynolds number effects on the blades through XFOIL calculations and wind tunnel measurements of airfoil 2D-section models. The resulting tower and wind turbine models have been tested for different operation states. The tower results are approximate and show low aerodynamic damping forces that can be neglected on the safe side. The measured aerodynamic damping forces of the operating turbine are compared to existing analytic approaches and to OpenFAST simulations. The measured values, although generally larger, show good agreement with the calculated ones. It is concluded that wind tunnel forced oscillations experiments could lead to a better characterization of the aerodynamic damping of wind turbines.